Activation of Wnt signaling promotes olaparib resistant ovarian cancer. Issue 10 (10th June 2019) - Yamamoto, Tomomi M.; McMellen, Alexandra; Watson, Zachary L.; Aguilera, Jennifer; Ferguson, Rebecca; Nurmemmedov, Elmar; Thakar, Tanay; Moldovan, George‐Lucian; Kim, Hyunmin; Cittelly, Diana M.; Joglar, Annette M.; Brennecke, Elyse P.; et al.
Abstract: Epithelial ovarian cancer (EOC) has one of the highest death to incidence ratios among all cancers. High grade serous ovarian carcinoma (HGSOC) is the most common and deadliest EOC histotype due to the lack of therapeutic options following debulking surgery and platinum/taxane‐based chemotherapies. For recurrent chemosensitive HGSOC, poly(ADP)‐ribose polymerase inhibitors (PARPi; olaparib, rucaparib, or niraparib) represent an emerging treatment strategy. While PARPi are most effective in homologous recombination DNA repair‐deficient (HRD) HGSOCs, recent studies have observed a significant benefit in non‐HRD HGSOCs. However, all HGSOC patients are likely to acquire resistance. Therefore, there is an urgent clinical need to understand PARPi resistance and to introduce novel combinatorial therapies to manage PARPi resistance and extend HGSOC disease‐free intervals. In a panel of HGSOC cell lines, we established matched olaparib sensitive and resistant cells. Transcriptome analysis of the matched olaparib‐sensitive vs ‐resistant cells revealed activation of the Wnt signaling pathway and consequently increased TCF transcriptional activity in PARPi‐resistant cells. Forced activation of canonical Wnt signaling in several PARPi‐sensitive cells via WNT3A reduced olaparib and rucaparib sensitivity. PARPi resistant cells were sensitive to inhibition of Wnt signaling using the FDA‐approved compound, pyrvinium pamoate, which has been shown to promote downregulation of β‐catenin. In both an HGSOC cell line and a patient‐derived xenograft model, we observed that combining pyrvinium pamoate with olaparib resulted in a significant decrease in tumor burden. This study demonstrates that Wnt signaling can mediate PARPi resistance in HGSOC and provides a clinical rationale for combining PARP and Wnt inhibitors.